Thorax Examination Procedure for TB in Supine and Erect Positions and Efforts to Prevent TB Virus Transmission to Radiographers - Muhammad Mirzaq Hakim; Hasmy, Achmad (Jurnal Kesehatan Cendikia Jenius, 2025)
Introduction: Chest radiology examination is an important procedure in diagnosing tuberculosis (TB); however, it may expose radiographers to radiation and increase the risk of infection transmission, making it necessary to evaluate the implementation of examination procedures and protective measures.Objective: This study aimed to evaluate clinical chest examination procedures for TB using supine and erect positions and to assess efforts to prevent TB transmission to radiographers at Hospital X.Methods: This study employed a qualitative descriptive design with a sample of 10 TB patients. Data were collected through direct observation, interviews with radiographers, and documentation review of standard operating procedures (SOPs) from January to May 2025, and were analyzed descriptively.Results: The findings indicated that the erect position produced more optimal image quality, while the supine position was used for patients with limited mobility. Transmission prevention measures included the use of personal protective equipment (PPE), masks, gloves, and equipment disinfection; however, compliance was not yet consistent. Education for patients and companions was also limited.Conclusion: It is concluded that optimization of examination procedures and improved adherence to safety protocols are essential. Strengthening safety education and continuous monitoring of PPE use are recommended.